Fully Programmable Collective Behavior of Light‐Powered Chemical Microrobotics: pH‐Dependent Motion Behavior Switch and Controlled Cancer Cell Destruction. (13th July 2022) - Dekanovsky, Lukas; Ying, Yulong; Zelenka, Jaroslav; Plutnar, Jan; Beladi‐Mousavi, Seyyed Mohsen; Křížová, Ivana; Novotný, Filip; Ruml, Tomáš; Pumera, Martin
Abstract: The development of fuel‐free light‐powered multi stimuli‐responsive microrobots is becoming a vital field in biomedical research. The challenge is to design biomedical robots with precise motion control and novel functionalities such that one day they will stand alongside medical staff as fully fledged partners in the delivery of advanced non‐invasive therapeutic procedures. In this study, a simple one‐step etching/polymerization procedure is used to fabricate crystalline metal‐organic framework structures surface‐coated with a conductive polypyrrole (PPy) layer and then enriched with Methylene Blue sensitizer molecules. Due to the PPy surface charge, the microrobots start to move when exposed to a visible light source, enabling the controllable accumulation of the microrobots at the focal point of the light beam. Furthermore, a self‐regulated motion is achieved by the PPy surface charge also providing a pH‐dependent switch capable of altering microrobot behavior. In vitro study is conducted to test microrobot efficiency against human cervix carcinoma HeLa cells. It is shown that the micromotors are able to penetrate and successfully destroy the cancer cells. The work provides proof‐of‐concept for a novel strategy in which such microrobots can be guided by an optical beam, can self‐regulate movement toward or away from each other, and can perform therapeutic functions with great efficiency. Abstract : Fuel‐free light‐powered microrobots with unique combination of materials enables them exceptional self‐regulatory and switchable collective behavior and also to penetrate and destroy cancer cells. Composed of metal‐organic framework crystals functionalized with polypyrrole and Methylene Blue sensitizer molecules, the microrobots show highly responsive light‐controlled motion behavior, rapidly navigating to and accumulating at the focal point of a visible light source.